100 Jahre Einkristallzucht aus der Schmelze: Vom Spreeknie ins Silicon Valley - Evers, Jürgen; Herzog, Christiane; Möckl, Leonhard; von Plotho, Christoph; Stallhofer, Peter; Staudigl, Rudolf (Chemie in Unserer Zeit, 2016)
Cars, television, mobile phones, digital cameras, cash machines: Daily life is strongly affected by microchips produced from high purity silicon single crystals via thin wafers. Most of these single crystals are prepared by a process invented by the German-Polish scientist Jan Czochralski in 1916 in the “Kabelwerk Oberspree (KWO)” of the “Allgemeine Elektricitätsgesellschaft (AEG)” in Berlin-Oberschöneweide. Czochralski discovered the famous method to pull single crystals by accident: Deep in thought, he dipped his pen not into an ink pot but into a crucible with liquid tin, both standing next to one another on his desk. Quickly he pulled his pen out and observed a thin thread of tin emerging from the tip. After etching, the thread was identified as a single crystal of tin. This observation is probably one of the most important technical inventions of the first half of the 20thcentury. In 1917, he left the AEG in Berlin and worked in the metal research laboratory, later belonging to the “Metallgesellschaft”, in Frankfurt/Main. Until today, wafers of high-purity silicon are prepared by the Czochralski method. Silicon wafers with 200 mm diameter were produced in 1990, 300 mm wafers in 2001. The production of wafers with 450 mm diameter was expected for 2016. Siltronic produced in 2009 the first dislocation-free silicon single crystal with 450 mm diameter, and other companies followed. However, until now, the 450 mm technology is not standard. This is due to a combination of very high investment costs needed to establish the 450 mm technology and very low prices of microchips.
CRIS-Team Scopus Importer:2024-09-09

Accurate and rapid background estimation in single-molecule localization microscopy using the deep neural network BGnet - Möckl, Leonhard; Roy, Anish R.; Petrov, Petar N.; Moerner, W. E. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Background fluorescence, especially when it exhibits undesired spatial features, is a primary factor for reduced image quality in optical microscopy. Structured background is particularly detrimental when analyzing single-molecule images for 3-dimensional localization microscopy or single-molecule tracking. Here, we introduce BGnet, a deep neural network with a U-net-type architecture, as a general method to rapidly estimate the background underlying the image of a point source with excellent accuracy, even when point-spread function (PSF) engineering is in use to create complex PSF shapes. We trained BGnet to extract the background from images of various PSFs and show that the identification is accurate for a wide range of different interfering background structures constructed from many spatial frequencies. Furthermore, we demonstrate that the obtained background-corrected PSF images, for both simulated and experimental data, lead to a substantial improvement in localization precision. Finally, we verify that structured background estimation with BGnet results in higher quality of superresolution reconstructions of biological structures.
CRIS-Team Scopus Importer:2024-09-09
Keywords: Background estimation; Deep learning; Localization microscopy; Single-molecule methods; Superresolution

Accurate phase retrieval of complex 3D point spread functions with deep residual neural networks - Möckl, Leonhard; Petrov, Petar N.; Moerner, W. E. (Applied Physics Letters, 2019)
Phase retrieval, i.e., the reconstruction of phase information from intensity information, is a central problem in many optical systems. Imaging the emission from a point source such as a single molecule is one example. Here, we demonstrate that a deep residual neural net is able to quickly and accurately extract the hidden phase for general point spread functions (PSFs) formed by Zernike-type phase modulations. Five slices of the 3D PSF at different focal positions within a two micrometer range around the focus are sufficient to retrieve the first six orders of Zernike coefficients.
CRIS-Team Scopus Importer:2024-09-09

A framework for the simulation of individual glycan coordinates to analyze spatial relationships within the glycocalyx - Fritsche, Sarah; Möckl, Leonhard (Frontiers in Cell and Developmental Biology, 2025)
The glycocalyx is a dense and dynamic layer of glycosylated species that covers every cell in the human body. It plays crucial roles in various cellular processes in health and disease, such as cancer immune evasion, cancer immune therapy, blastocyst implantation, and functional attenuation of membrane protein diffusion. In addition, alterations in glycocalyx structure may play an important role in ocular surface diseases, e.g., dry eye disease. Despite the emerging importance of the glycocalyx, various aspects of its functional organization remain elusive to date. A central reason for this elusiveness is the nanoscale dimension of the glycocalyx in conjunction with its high structural complexity, which is not accessible to observation with conventional light microscopy. Recent advances in super-resolution microscopy have enabled resolutions down to the single-digit nanometer range. In order to fully leverage the potential of these novel methods, computational frameworks that allow for contextualization of the resulting experimental data are required. Here, we present a simulation-based approach to analyze spatial relationships of glycan components on the cell membrane based on known geometrical parameters. We focus on sialic acids in this work, but the technique can be adapted to any glycan component of interest. By integrating data from mass spectrometry and quantitative biological studies, these simulations aim to model possible experimental outcomes, which can then be used for further analysis, such as spatial point statistics. Importantly, we include various experimental considerations, such as labeling and detection efficiency. This approach may contribute to establishing a new standard of connection between geometrical and molecular-resolution data in service of advancing our understanding of the functional role of the glycocalyx in biology as well as its clinical potential.
CRIS-Team Scopus Importer:2025-02-04
Keywords: computational methods; glycocalyx; mucins; ocular glycocalyx; quantitative biology; sialic acids; simulation; super-resolution microscopy

A paintbrush for delivery of nanoparticles and molecules to live cells with precise spatiotemporal control - Holler, Cornelia; Taylor, Richard William; Schambony, Alexandra; Möckl, Leonhard; Sandoghdar, Vahid (Nature methods, 2024)
Delivery of very small amounts of reagents to the near-field of cells with micrometer spatial precision and millisecond time resolution is currently out of reach. Here we present μkiss as a micropipette-based scheme for brushing a layer of small molecules and nanoparticles onto the live cell membrane from a subfemtoliter confined volume of a perfusion flow. We characterize our system through both experiments and modeling, and find excellent agreement. We demonstrate several applications that benefit from a controlled brush delivery, such as a direct means to quantify local and long-range membrane mobility and organization as well as dynamical probing of intercellular force signaling.
CRIS-Team Scopus Importer:2024-02-23

A Photoswitchable Trivalent Cluster Mannoside to Probe the Effects of Ligand Orientation in Bacterial Adhesion - Despras, Guillaume; Möckl, Leonhard; Heitmann, Anne; Stamer, Insa; Bräuchle, Christoph; Lindhorst, Thisbe K. (ChemBioChem, 2019)
We have recently demonstrated, by employing azobenzene glycosides, that bacterial adhesion to surfaces can be switched through reversible reorientation of the carbohydrate ligands. To investigate this phenomenon further, we have turned here to more complex—that is, multivalent—azobenzene glycoclusters. We report on the synthesis of a photosensitive trivalent cluster mannoside conjugated to an azobenzene hinge at the focal point. Molecular dynamics studies suggested that this cluster mannoside, despite the conformational flexibility of the azobenzene-glycocluster linkage, offers the potential for reversibly changing the glycocluster's orientation on a surface. Next, the photoswitchable glycocluster was attached to human cells, and adhesion assays with type 1 fimbriated Escherichia coli bacteria were performed. They showed marked differences in bacterial adhesion, dependent on the light-induced reorientation of the glycocluster moiety. These results further underline the importance of orientational effects in carbohydrate recognition and likewise the value of photoswitchable glycoconjugates for their study.
CRIS-Team Scopus Importer:2024-09-09
Keywords: cell adhesion; control of carbohydrate recognition; metabolic oligosaccharide engineering; multivalency; photochemistry

Artificial Formation and Tuning of Glycoprotein Networks on Live Cell Membranes: A Single-Molecule Tracking Study - Möckl, Leonhard; Lindhorst, Thisbe K.; Bräuchle, Christoph (ChemPhysChem, 2016)
We present a method to artificially induce network formation of membrane glycoproteins and show the precise tuning of their interconnection on living cells. For this, membrane glycans are first metabolically labeled with azido sugars and then tagged with biotin by copper-free click chemistry. Finally, these biotin-tagged membrane proteins are interconnected with streptavidin (SA) to form an artificial protein network in analogy to a lectin-induced lattice. The degree of network formation can be controlled by the concentration of SA, its valency, and the concentration of biotin on membrane proteins. This was verified by investigation of the spatiotemporal dynamics of the SA-protein networks employing single-molecule tracking. It was also proven that this network formation strongly influences the biologically relevant process of endocytosis as it is known from natural lattices on the cell surface.
CRIS-Team Scopus Importer:2024-09-09
Keywords: artificial protein networks; endocytosis; glycoprotein engineering; membrane proteins; single-molecule tracking

Automated discovery of experimental designs in super-resolution microscopy with XLuminA - Rodríguez, Carla; Arlt, Sören; Möckl, Leonhard; Krenn, Mario (Nature Communications, 2024)
Driven by human ingenuity and creativity, the discovery of super-resolution techniques, which circumvent the classical diffraction limit of light, represent a leap in optical microscopy. However, the vast space encompassing all possible experimental configurations suggests that some powerful concepts and techniques might have not been discovered yet, and might never be with a human-driven direct design approach. Thus, AI-based exploration techniques could provide enormous benefit, by exploring this space in a fast, unbiased way. We introduce XLuminA, an open-source computational framework developed using JAX, a high-performance computing library in Python. XLuminA offers enhanced computational speed enabled by JAX’s accelerated linear algebra compiler (XLA), just-in-time compilation, and its seamlessly integrated automatic vectorization, automatic differentiation capabilities and GPU compatibility. XLuminA demonstrates a speed-up of 4 orders of magnitude compared to well-established numerical optimization methods. We showcase XLuminA’s potential by re-discovering three foundational experiments in advanced microscopy, and identifying an unseen experimental blueprint featuring sub-diffraction imaging capabilities. This work constitutes an important step in AI-driven scientific discovery of new concepts in optics and advanced microscopy.
CRIS-Team Scopus Importer:2025-02-04

Azido Pentoses: A New Tool To Efficiently Label Mycobacterium tuberculosis Clinical Isolates - Kolbe, Katharina; Möckl, Leonhard; Sohst, Victoria; Brandenburg, Julius; Engel, Regina; Malm, Sven; Bräuchle, Christoph; Holst, Otto; Lindhorst, Thisbe K.; Reiling, Norbert (ChemBioChem, 2017)
Mycobacterium tuberculosis (Mtb), the main causative agent of tuberculosis (Tb), has a complex cell envelope which forms an efficient barrier to antibiotics, thus contributing to the challenges of anti-tuberculosis therapy. However, the unique Mtb cell wall can be considered an advantage and be utilized to selectively label Mtb bacteria. Here we introduce three azido pentoses as new compounds for metabolic labeling of Mtb: 3-azido arabinose (3AraAz), 3-azido ribose (3RiboAz), and 5-azido arabinofuranose (5AraAz). 5AraAz demonstrated the highest level of Mtb labeling and was efficiently incorporated into the Mtb cell wall. All three azido pentoses can be easily used to label a variety of Mtb clinical isolates without influencing Mtb-dependent phagosomal maturation arrest in infection studies with human macrophages. Thus, this metabolic labeling method offers the opportunity to attach desired molecules to the surface of Mtb bacteria in order to facilitate investigation of the varying virulence characteristics of different Mtb clinical isolates, which influence the outcome of a Tb infection.
CRIS-Team Scopus Importer:2024-09-09
Keywords: arabinan metabolism; carbohydrates; click chemistry; metabolic labeling; Mycobacterium tuberculosis

Bisacylphosphane oxides as photo-latent cytotoxic agents and potential photo-latent anticancer drugs - Beil, Andreas; Steudel, Friederike A.; Bräuchle, Christoph; Grützmacher, Hansjörg; Möckl, Leonhard (Scientific Reports, 2019)
Bisacylphosphane oxides (BAPOs) are established as photoinitiators for industrial applications. Light irradiation leads to their photolysis, producing radicals. Radical species induce oxidative stress in cells and may cause cell death. Hence, BAPOs may be suitable as photolatent cytotoxic agents, but such applications have not been investigated yet. Herein, we describe for the first time a potential use of BAPOs as drugs for photolatent therapy. We show that treatment of the breast cancer cell lines MCF-7 and MDA-MB-231 and of breast epithelial cells MCF-10A with BAPOs and UV irradiation induces apoptosis. Cells just subjected to BAPOs or UV irradiation alone are not affected. The induction of apoptosis depend on the BAPO and the irradiation dose. We proved that radicals are the active species since cells are rescued by an antioxidant. Finally, an optimized BAPO-derivative was designed which enters the cells more efficiently and thus leads to stronger effects at lower doses.
CRIS-Team Scopus Importer:2024-09-09

Cell-penetrating and neurotargeting dendritic siRNA nanostructures - Brunner, Korbinian; Harder, Johannes; Halbach, Tobias; Willibald, Julian; Spada, Fabio; Gnerlich, Felix; Sparrer, Konstantin; Beil, Andreas; Möckl, Leonhard; Bräuchle, Christoph; Conzelmann, Karl Klaus; Carell, Thomas (Angewandte Chemie International Edition, 2015)
We report the development of dendritic siRNA nanostructures that are able to penetrate even difficult to transfect cells such as neurons with the help of a special receptor ligand. The nanoparticles elicit strong siRNA responses, despite the dendritic structure. An siRNA dendrimer directed against the crucial rabies virus (RABV) nucleoprotein (N protein) and phosphoprotein (P protein) allowed the suppression of the virus titer in neurons below the detection limit. The cell-penetrating siRNA dendrimers, which were assembled using click chemistry, open up new avenues toward finding novel molecules able to cure this deadly disease.
CRIS-Team Scopus Importer:2024-09-09
Keywords: Anandamide; Antiviral agents; Drug delivery; Gene silencing; Stem cells

Deep learning in single-molecule microscopy: Fundamentals, caveats, and recent developments [Invited] - Möckl, Leonhard; Roy, Anish R.; Moerner, W. E. (Biomedical Optics Express, 2020)
Deep learning-based data analysis methods have gained considerable attention in all fields of science over the last decade. In recent years, this trend has reached the single-molecule community. In this review, we will survey significant contributions of the application of deep learning in single-molecule imaging experiments. Additionally, we will describe the historical events that led to the development of modern deep learning methods, summarize the fundamental concepts of deep learning, and highlight the importance of proper data composition for accurate, unbiased results.
CRIS-Team Scopus Importer:2024-09-09

Dendrimer-Based Signal Amplification of Click-Labelled DNA in Situ - Raddaoui, Nada; Stazzoni, Samuele; Möckl, Leonhard; Viverge, Bastien; Geiger, Florian; Engelke, Hanna; Bräuchle, Christoph; Carell, Thomas (ChemBioChem, 2017)
The in vivo incorporation of alkyne-modified bases into the genome of cells is today the basis for the efficient detection of cell proliferation. Cells are grown in the presence of ethinyl-dU (EdU), fixed and permeabilised. The incorporated alkynes are then efficiently detected by using azide-containing fluorophores and the CuI-catalysed alkyne–azide click reaction. For a world in which constant improvement in the sensitivity of a given method is driving diagnostic advancement, we developed azide- and alkyne-modified dendrimers that allow the establishment of sandwich-type detection assays that show significantly improved signal intensities and signal-to-noise ratios far beyond that which is currently possible.
CRIS-Team Scopus Importer:2024-09-09
Keywords: cell proliferation; click chemistry; dendrimers; fluorescence microscopy; high-throughput screening

Die Fraunhofer-Gesellschaft: Von kleinen Anfängen zum steilen Aufstieg - Evers, Jürgen; Herzog, Christiane; Möckl, Leonhard (Chemie in Unserer Zeit, 2021)
The Fraunhofer-Gesellschaft (FhG) was founded by the Secretary of the Baverian Ministry of Economics, Hugo Geiger. He intended to create a research organisation that should unite science and economics to foster applied research. The new institution was named after Joseph von Fraunhofer, a hint to its intended orientation as Fraunhofer was both an ingenious scientist and a successful businessman. His inventions were developed into products which were sold all over the word. The FhG as new organisation would become the third pillar of German Research next to the Max-Planck-Society (MPG) and the German Research Foundation (DFG), but initially, the MPG and the DFG caused some problems for the newly founded FhG. However, when the German Ministry for Research guaranteed funding, the FhG quickly rose to international recognition.
CRIS-Team Scopus Importer:2024-09-09

En route from artificial to natural: Evaluation of inhibitors of mannose-specific adhesion of E. coli under flow - Möckl, Leonhard; Fessele, Claudia; Despras, Guillaume; Bräuchle, Christoph; Lindhorst, Thisbe K. (Biochimica et Biophysica Acta - General Subjects, 2016)
We investigated the properties of six Escherichia coli adhesion inhibitors under static and under flow conditions. On mannan-covered model substrates and under static conditions, all inhibitors were able to almost completely abolish lectin-mediated E. coli adhesion. On a monolayer of living human microvascular endothelial cells (HMEC-1), the inhibitors reduced adhesion under static conditions as well, but a large fraction of bacteria still managed to adhere even at highest inhibitor concentrations. In contrast, under flow conditions E. coli did not exhibit any adhesion to HMEC-1 not even at inhibitor concentrations where significant adhesion was detected under static conditions. This indicates that the presence of shear stress strongly affects inhibitor properties and must be taken into account when evaluating the potency of bacterial adhesion inhibitors.
CRIS-Team Scopus Importer:2024-09-09
Keywords: Antiadhesion therapy; Bacterial adhesion; Carbohydrate recognition; Flow conditions; Shear stress

Erratum to “Small molecule inhibitors of mammalian glycosylation” [Matrix Biol. Plus 16C (2022) 100108] (Matrix Biology Plus (2022) 16, (S2590028522000084), (10.1016/j.mbplus.2022.100108)) - Almahayni, Karim; Spiekermann, Malte; Fiore, Antonio; Yu, Guoqiang; Pedram, Kayvon; Möckl, Leonhard (Matrix Biology Plus, 2022)
This article was temporarily removed in April 2022 due to production errors by the publisher. The publisher apologizes for any inconvenience caused.
CRIS-Team Scopus Importer:2024-09-09

Fluorophores’ talk turns them dark - Almahayni, Karim; Spiekermann, Malte; Möckl, Leonhard (Nature methods, 2022)
CRIS-Team Scopus Importer:2024-09-09

From Biophysics to Biomedical Physics - Almahayni, Karim; Bachir Salvador, Jana; Moonnukandathil Joseph, Dijo; Yurekli, Nazlican; Möllmert, Stephanie; Möckl, Leonhard (ACS Bio & Med Chem Au, 2024)
The intersection of physics and medicine has long been a fertile ground for innovation, with advances in one field driving breakthroughs in the other. In recent years, the emergence of modern biophysical techniques has provided a toolbox for understanding complex physiological processes across scales. These tools have the potential to revolutionize medical practice, from diagnosis to therapy. However, despite this immense potential, the path from basic biophysical research to clinical translation remains fraught with challenges. This review aims to highlight emerging biophysical tools and their potential applications in medical physics, with a focus on how these innovations can be translated into clinical solutions. We outline a strategic roadmap for bridging the gap between cutting-edge biophysics research and its effective integration into clinical settings, ensuring that these technologies can meaningfully transform patient care.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Biophysics; Clinical biology; Mechanical phenotyping; Medicine; Microscopy; Super-resolution microscopy; Translational medicine

Genome-wide CRISPR screens reveal a specific ligand for the glycan-binding immune checkpoint receptor Siglec-7 - Wisnovsky, Simon; Möckl, Leonhard; Malaker, Stacy A.; Pedram, Kayvon; Hess, Gaelen T.; Riley, Nicholas M.; Gray, Melissa A.; Smith, Benjamin A.H.; Bassik, Michael C.; Moerner, W. E.; Bertozzi, Carolyn R. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Glyco-immune checkpoint receptors, molecules that inhibit immune cell activity following binding to glycosylated cell-surface antigens, are emerging as attractive targets for cancer immunotherapy. Defining biologically relevant ligands that bind and activate such receptors, however, has historically been a significant challenge. Here, we present a CRISPRi genomic screening strategy that allowed unbiased identification of the key genes required for cell-surface presentation of glycan ligands on leukemia cells that bind the glyco-immune checkpoint receptors Siglec-7 and Siglec-9. This approach revealed a selective interaction between Siglec-7 and the mucin-type glycoprotein CD43. Further work identified a specific N-terminal glycopeptide region of CD43 containing clusters of disialylated O-glycan tetrasaccharides that form specific Siglec-7 binding motifs. Knockout or blockade of CD43 in leukemia cells relieves Siglec-7-mediated inhibition of immune killing activity. This work identifies a potential target for immune checkpoint blockade therapy and represents a generalizable approach to dissection of glycan–receptor interactions in living cells.
CRIS-Team Scopus Importer:2024-09-09
Keywords: CRISPR Screening; Glycobiology; Tumor Immunology

Invasiveness of Cells Leads to Changes in Their Interaction Behavior with the Glycocalyx - Broda, Ellen; Torrano, Adriano A.; Löbbert, Laura; Möckl, Leonhard; Bräuchle, Christoph; Engelke, Hanna (Advanced Biosystems, 2018)
Transendothelial migration is a crucial step during metastasis. Before circulating tumor cells enter the endothelium, they face the glycocalyx. While invasive migration of cancer cells is well studied, few investigations exist regarding their interaction with the glycocalyx. Here, the interaction of three breast cell lines with an endothelial glycocalyx is studied. Benign MCF-10A, noninvasive malign MCF-7, and invasive MDA-MB-231 cells penetrate the glycocalyx, just adhere to it or approach without even attaching to it. Remarkable fluctuations in these interaction modes are detected by time-resolved interaction profiles. Adhesion, migration, and invasion characteristics as well as combinations of interaction modes, cell shapes, and cell extensions are studied. The motility and penetration depth into the glycocalyx are analyzed. The invasive cells are the most flexible, penetrating the glycocalyx mostly with a round shape and feet-like membrane extensions. Noninvasive cancer cells penetrate the glycocalyx the deepest over time and benign cells integrate more likely into the endothelial cell layer underneath the glycocalyx.
CRIS-Team Scopus Importer:2024-09-09
Keywords: cell invasion; cell migration; glycocalyx; time-lapse imaging; transendothelial migration

Microdomain Formation Controls Spatiotemporal Dynamics of Cell-Surface Glycoproteins - Möckl, Leonhard; Horst, Andrea K.; Kolbe, Katharina; Lindhorst, Thisbe K.; Bräuchle, Christoph (ChemBioChem, 2015)
The effect of galectin-mediated microdomain formation on the spatiotemporal dynamics of glycosylated membrane proteins in human microvascular endothelial cells (HMEC-1) was studied qualitatively and quantitatively by high-resolution fluorescence microscopy and artificially mimicked by metabolic glycoprotein engineering. Two types of membrane proteins, sialic acid-bearing proteins (SABPs) and mucin-type proteins (MTPs), were investigated. For visualization they were metabolically labeled with azido sugars and then coupled to a cyclooctyne-conjugated fluorescent dye by click chemistry. Both spatial (diffusion) and temporal (residence time) dynamics of SABPs and MTPs on the membrane were investigated after treatment with exogenous galectin-1 or -3. Strong effects of galectin-mediated lattice formation were observed for MTPs (decreased spatial mobility), but not for SABPs. Lattice formation also strongly decreased the turnover of MTPs (increased residence time on the cell membrane). The effects of galectin-mediated crosslinking was accurately mimicked by streptavidin-mediated crosslinking of biotin-tagged glycoproteins and verified by single-molecule tracking. This technique allows the induction of crosslinking of membrane proteins under precisely controlled conditions, thereby influencing membrane residence time and the spatial dynamics of glycans on the cell membrane in a controlled way.
CRIS-Team Scopus Importer:2024-09-09
Keywords: galectin lattice; glycosylation; lattice mimicking; membrane proteins; single-molecule tracking

More Than 50 Years after Its Discovery in SiO2 Octahedral Coordination Has Also Been Established in SiS2 at High Pressure - Evers, Jürgen; Möckl, Leonhard; Oehlinger, Gilbert; Köppe, Ralf; Schnöckel, Hansgeorg; Barkalov, Oleg; Medvedev, Sergey; Naumov, Pavel (Inorganic Chemistry, 2017)
SiO2 exhibits a high-pressure-high-temperature polymorphism, leading to an increase in silicon coordination number and density. However, for the related compound SiS2 such pressure-induced behavior has not been observed with tetrahedral coordination yet. All four crystal structures of SiS2 known so far contain silicon with tetrahedral coordination. In the orthorhombic, ambient-pressure phase these tetrahedra share edges and achieve only low space filling and density. Up to 4 GPa and 1473 K, three phases can be quenched as metastable phases from high-pressure high-temperature to ambient conditions. Space occupancy and density are increased first by edge and corner sharing and then by corner sharing alone. The structural situation of SiS2 up to the current study resembles that of SiO2 in 1960: Then, in its polymorphs only Si-O4 tetrahedra were known. But in 1961, a polymorph with rutile structure was discovered: octahedral Si-O6 coordination was established. Now, 50 years later, we report here on the transition from 4-fold to 6-fold coordination in SiS2, the sulfur analogue of silica.
CRIS-Team Scopus Importer:2024-09-09

Multi-color super-resolution imaging to study human coronavirus RNA during cellular infection - Wang, Jiarui; Han, Mengting; Roy, Anish R.; Wang, Haifeng; Möckl, Leonhard; Zeng, Leiping; Moerner, W. E.; Qi, Lei S. (Cell Reports: Methods, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the third human coronavirus within 20 years that gave rise to a life-threatening disease and the first to reach pandemic spread. To make therapeutic headway against current and future coronaviruses, the biology of coronavirus RNA during infection must be precisely understood. Here, we present a robust and generalizable framework combining high-throughput confocal and super-resolution microscopy imaging to study coronavirus infection at the nanoscale. Using the model human coronavirus HCoV-229E, we specifically labeled coronavirus genomic RNA (gRNA) and double-stranded RNA (dsRNA) via multi-color RNA immunoFISH and visualized their localization patterns within the cell. The 10-nm resolution achieved by our approach uncovers a striking spatial organization of gRNA and dsRNA into three distinct structures and enables quantitative characterization of the status of the infection after antiviral drug treatment. Our approach provides a comprehensive imaging framework that will enable future investigations of coronavirus fundamental biology and therapeutic effects.
CRIS-Team Scopus Importer:2024-09-09
Keywords: coronavirus infection model; ER remodeling; FISH; fluorescence imaging; human coronavirus 229E; Remdesivir; RNA localization; spike protein; super-resolution microscopy; viral replication and infection

New insights into the intracellular distribution pattern of cationic amphiphilic drugs - Vater, Magdalena; Möckl, Leonhard; Gormanns, Vanessa; Schultz Fademrecht, Carsten; Mallmann, Anna M.; Ziegart-Sadowska, Karolina; Zaba, Monika; Frevert, Marie L.; Bräuchle, Christoph; Holsboer, Florian; Rein, Theo; Schmidt, Ulrike; et al. (Scientific Reports, 2017)
Cationic amphiphilic drugs (CADs) comprise a wide variety of different substance classes such as antidepressants, antipsychotics, and antiarrhythmics. It is well recognized that CADs accumulate in certain intracellular compartments leading to specific morphological changes of cells. So far, no adequate technique exists allowing for ultrastructural analysis of CAD in intact cells. Azidobupramine, a recently described multifunctional antidepressant analogue, allows for the first time to perform high-resolution studies of CADs on distribution pattern and morphological changes in intact cells. We showed here that the intracellular distribution pattern of azidobupramine strongly depends on drug concentration and exposure time. The mitochondrial compartment (mDsRed) and the late endo-lysosomal compartment (CD63-GFP) were the preferred localization sites at low to intermediate concentrations (i.e. 1 μM, 5 μM). In contrast, the autophagosomal compartment (LC3-GFP) can only be reached at high concentrations (10 μM) and long exposure times (72 hrs). At the morphological level, LC3-clustering became only prominent at high concentrations (10 μM), while changes in CD63 pattern already occurred at intermediate concentrations (5 μM). To our knowledge, this is the first study that establishes a link between intracellular CAD distribution pattern and morphological changes. Therewith, our results allow for gaining deeper understanding of intracellular effects of CADs.
CRIS-Team Scopus Importer:2024-09-09

Optical investigations clarify a puzzle: The Wittelsbach and the Hope diamonds Der wittelsbacher und der hope-diamant: Optische untersuchungen klären ein rätsel - Evers, Jürgen; Möckl, Leonhard; Nöth, Heinrich (Chemie in Unserer Zeit, 2012)
Diamonds are formed from carbon at high pressures and high temperatures in the inner part of the earth. Doping with very small amounts of boron leads to diamonds with blue colour. Two of the most famous historical blue diamonds, the Wittelsbach and Hope Diamond, were found in the Indian Kollur mine. The latter was brought to Europe by the French gem merchant Tavernier. Today it is displayed in the Smithsonian Institute. The Wittelsbach Diamond was for a long time in the possession of the House Wittelsbach until it was secretly sold in Antwerp in 1951. In 2008, it was purchased by auction by the jeweller Graff who recut the gem. In 2011, it was sold to an unknown buyer. As the Wittelsbach and the Hope diamond share origin and colour, it was assumed for a long time that both are pieces from a larger crystal. By optical investigation it was now shown that they have indeed some similar optical properties, but differ strikingly in other ones. Hence, they cannot originate from the same crystal. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2024-09-09
Keywords: Bor; Diamanten; Hope; Kollur; Phosphoreszenz; Tatami-Muster; Versetzungen; Wittelsbacher

Physical Principles of Membrane Shape Regulation by the Glycocalyx - Shurer, Carolyn R.; Kuo, Joe Chin Hun; Roberts, La Deidra Monét; Gandhi, Jay G.; Colville, Marshall J.; Enoki, Thais A.; Pan, Hao; Su, Jin; Noble, Jade M.; Hollander, Michael J.; O'Donnell, John P.; Yin, Rose; et al. (Cell, 2019)
Cells bend their plasma membranes into highly curved forms to interact with the local environment, but how shape generation is regulated is not fully resolved. Here, we report a synergy between shape-generating processes in the cell interior and the external organization and composition of the cell-surface glycocalyx. Mucin biopolymers and long-chain polysaccharides within the glycocalyx can generate entropic forces that favor or disfavor the projection of spherical and finger-like extensions from the cell surface. A polymer brush model of the glycocalyx successfully predicts the effects of polymer size and cell-surface density on membrane morphologies. Specific glycocalyx compositions can also induce plasma membrane instabilities to generate more exotic undulating and pearled membrane structures and drive secretion of extracellular vesicles. Together, our results suggest a fundamental role for the glycocalyx in regulating curved membrane features that serve in communication between cells and with the extracellular matrix.
CRIS-Team Scopus Importer:2024-09-09
Keywords: cancer; glycocalyx; hyaluronic acid; membrane curvature; membrane morphology; membrane organelle; microvesicle; microvilli; Muc1; mucin

Quantitative Super-Resolution Microscopy of the Mammalian Glycocalyx - Möckl, Leonhard; Pedram, Kayvon; Roy, Anish R.; Krishnan, Venkatesh; Gustavsson, Anna Karin; Dorigo, Oliver; Bertozzi, Carolyn R.; Moerner, W. E. (Developmental Cell, 2019)
The mammalian glycocalyx is a heavily glycosylated extramembrane compartment found on nearly every cell. Despite its relevance in both health and disease, studies of the glycocalyx remain hampered by a paucity of methods to spatially classify its components. We combine metabolic labeling, bioorthogonal chemistry, and super-resolution localization microscopy to image two constituents of cell-surface glycans, N-acetylgalactosamine (GalNAc) and sialic acid, with 10–20 nm precision in 2D and 3D. This approach enables two measurements: glycocalyx height and the distribution of individual sugars distal from the membrane. These measurements show that the glycocalyx exhibits nanoscale organization on both cell lines and primary human tumor cells. Additionally, we observe enhanced glycocalyx height in response to epithelial-to-mesenchymal transition and to oncogenic KRAS activation. In the latter case, we trace increased height to an effector gene, GALNT7. These data highlight the power of advanced imaging methods to provide molecular and functional insights into glycocalyx biology. Nearly every cell in the human body is encapsulated by an extramembrane glycosylated compartment—the glycocalyx—that is the cell's first point of contact with the extracellular environment. Möckl et al. combine bioorthogonal chemistry with quantitative super-resolution imaging to investigate glycocalyx nanoscale organization and its relationship to oncogenic cellular transformation.
CRIS-Team Scopus Importer:2024-09-09
Keywords: bioorthogonal chemistry; GALNT7; glycobiology; glycocalyx; KRAS; membrane biophysics; metabolic labeling; ovarian cancer; pancreatic adenocarcinoma; super-resolution microscopy

RNA-binding proteins and glycoRNAs form domains on the cell surface for cell-penetrating peptide entry - Perr, Jonathan; Langen, Andreas; Almahayni, Karim; Nestola, Gianluca; Chai, Peiyuan; Lebedenko, Charlotta G.; Volk, Regan F.; Detrés, Diego; Caldwell, Reese M.; Spiekermann, Malte; Hemberger, Helena; Bisaria, Namita; et al. (Cell, 2025)
The composition and organization of the cell surface determine how cells interact with their environment. Traditionally, glycosylated transmembrane proteins were thought to be the major constituents of the external surface of the plasma membrane. Here, we provide evidence that a group of RNA-binding proteins (RBPs) is present on the surface of living cells. These cell-surface RBPs (csRBPs) precisely organize into well-defined nanoclusters enriched for multiple RBPs and glycoRNAs, and their clustering can be disrupted by extracellular RNase addition. These glycoRNA-csRBP clusters further serve as sites of cell-surface interaction for the cell-penetrating peptide trans-activator of transcription (TAT). Removal of RNA from the cell surface, or loss of RNA-binding activity by TAT, causes defects in TAT cell internalization. Together, we provide evidence of an expanded view of the cell surface by positioning glycoRNA-csRBP clusters as a regulator of communication between cells and the extracellular environment.
CRIS-Team Scopus Importer:2025-04-01
Keywords: cell surface; cell-penetrating peptides; glycoRNA; RNA-binding proteins

Setting the stage for universal pharmacological targeting of the glycocalyx - Almahayni, Karim; Möckl, Leonhard (Current Topics in Membranes, 2023)
All cells in the human body are covered by a complex meshwork of sugars as well as proteins and lipids to which these sugars are attached, collectively termed the glycocalyx. Over the past few decades, the glycocalyx has been implicated in a range of vital cellular processes in health and disease. Therefore, it has attracted considerable interest as a therapeutic target. Considering its omnipresence and its relevance for various areas of cell biology, the glycocalyx should be a versatile platform for therapeutic intervention, however, the full potential of the glycocalyx as therapeutic target is yet to unfold. This might be attributable to the fact that glycocalyx alterations are currently discussed mainly in the context of specific diseases. In this perspective review, we shift the attention away from a disease-centered view of the glycocalyx, focusing on changes in glycocalyx state. Furthermore, we survey important glycocalyx-targeted drugs currently available and finally discuss future steps. We hope that this approach will inspire a unified, holistic view of the glycocalyx in disease, helping to stimulate novel glycocalyx-targeted therapy strategies.
CRIS-Team Scopus Importer:2024-09-09
Keywords: cancer; Glycobiology; Glycocalyx; Pharmacology; Therapeutics; Vascular biology

Simple, Economic, and Robust Rail-Based Setup for Super-Resolution Localization Microscopy - Almahayni, Karim; Almahayni, Karim; Nestola, Gianluca; Spiekermann, Malte; Möckl, Leonhard (Journal of Physical Chemistry A, 2023)
Research during the past 2 decades has showcased the power of single-molecule localization microscopy (SMLM) as a tool for exploring the nanoworld. However, SMLM systems are typically available in specialized laboratories and imaging facilities, owing to their expensiveness as well as complex assembly and alignment procedure. Here, we lay out the blueprint of a sturdy, rail-based, cost-efficient, multicolor SMLM setup that is easy to construct and align in service of simplifying the accessibility of SMLM. We characterize the optical properties of the design and assess its capabilities, robustness, and stability. The performance of the system is assayed using super-resolution imaging of biological samples. We believe that this design will make SMLM more affordable and broaden its availability.
CRIS-Team Scopus Importer:2023-06-09

Small molecule inhibitors of mammalian glycosylation - Almahayni, Karim; Spiekermann, Malte; Fiore, Antonio; Yu, Guoqiang; Pedram, Kayvon; Möckl, Leonhard (Matrix Biology Plus, 2022)
Glycans are one of the fundamental biopolymers encountered in living systems. Compared to polynucleotide and polypeptide biosynthesis, polysaccharide biosynthesis is a uniquely combinatorial process to which interdependent enzymes with seemingly broad specificities contribute. The resulting intracellular cell surface, and secreted glycans play key roles in health and disease, from embryogenesis to cancer progression. The study and modulation of glycans in cell and organismal biology is aided by small molecule inhibitors of the enzymes involved in glycan biosynthesis. In this review, we survey the arsenal of currently available inhibitors, focusing on agents which have been independently validated in diverse systems. We highlight the utility of these inhibitors and drawbacks to their use, emphasizing the need for innovation for basic research as well as for therapeutic applications.
CRIS-Team Scopus Importer:2024-09-09
Keywords: Glycans; Glycocalyx; Glycosylation; Inhibitors; Small molecules

Super-resolution Microscopy with Single Molecules in Biology and Beyond-Essentials, Current Trends, and Future Challenges - Möckl, Leonhard; Moerner, W. E. (Journal of the American Chemical Society, 2020)
Single-molecule super-resolution microscopy has developed from a specialized technique into one of the most versatile and powerful imaging methods of the nanoscale over the past two decades. In this perspective, we provide a brief overview of the historical development of the field, the fundamental concepts, the methodology required to obtain maximum quantitative information, and the current state of the art. Then, we will discuss emerging perspectives and areas where innovation and further improvement are needed. Despite the tremendous progress, the full potential of single-molecule super-resolution microscopy is yet to be realized, which will be enabled by the research ahead of us.
CRIS-Team Scopus Importer:2024-09-09

Supersensitive Multifluorophore RNA-FISH for Early Virus Detection and Flow-FISH by Using Click Chemistry - Raddaoui, Nada; Croce, Stefano; Geiger, Florian; Borodavka, Alexander; Möckl, Leonhard; Stazzoni, Samuele; Viverge, Bastien; Bräuchle, Christoph; Frischmuth, Thomas; Engelke, Hanna; Carell, Thomas (ChemBioChem, 2020)
The reliable detection of transcription events through the quantification of the corresponding mRNA is of paramount importance for the diagnostics of infections and diseases. The quantification and localization analysis of the transcripts of a particular gene allows disease states to be characterized more directly compared to an analysis on the transcriptome wide level. This is particularly needed for the early detection of virus infections as now required for emergent viral diseases, e. g. Covid-19. In situ mRNA analysis, however, is a formidable challenge and currently performed with sets of single-fluorophore-containing oligonucleotide probes that hybridize to the mRNA in question. Often a large number of probe strands (>30) are required to get a reliable signal. The more oligonucleotide probes are used, however, the higher the potential off-target binding effects that create background noise. Here, we used click chemistry and alkyne-modified DNA oligonucleotides to prepare multiple-fluorophore-containing probes. We found that these multiple-dye probes allow reliable detection and direct visualization of mRNA with only a very small number (5–10) of probe strands. The new method enabled the in situ detection of viral transcripts as early as 4 hours after infection.
CRIS-Team Scopus Importer:2024-09-09
Keywords: click chemistry; fluorescence probes; mRNA detection; RNA-FISH; viral infection

Switching first contact: Photocontrol of E. coli adhesion to human cells - Möckl, Leonhard; Müller, A.; Bräuchle, C.; Lindhorst, T. K. (Chemical Communications, 2016)
We have shown previously that carbohydrate-specific bacterial adhesion to a non-physiological surface can be photocontrolled by reversible E/Z isomerisation using azobenzene-functionalised sugars. Here, this approach is applied to the surface of human cells. We show not only that bacterial adhesion to the azobenzene glycoside-modified cell surface is higher in the E than in the Z state, but add data about the specific modulation of the effect.
CRIS-Team Scopus Importer:2024-09-09

Tailored Bisacylphosphane Oxides for Precise Induction of Oxidative Stress-Mediated Cell Death in Biological Systems - Almahayni, Karim; Bachir Salvador, Jana; Conti, Riccardo; Widera, Anna; Spiekermann, Malte; Wehner, Daniel; Grützmacher, Hansjörg; Möckl, Leonhard (ACS Chemical Biology, 2024)
Precise cell elimination within intricate cellular populations is hampered by issues arising from the multifaceted biological properties of cells and the expansive reactivity of chemical agents. Current chemical platforms are often limited by their complexity, toxicity, and poor physical/chemical properties. Here, we report on the synthesis of a structurally versatile library of chemically tunable bisacylphosphane oxides (BAPOs), which harnesses the spatiotemporal precision of light delivery, thereby establishing a universal strategy for on-demand, precise cellular ablation in vitro and in viv
Keywords: Assays; Cells; Irradiation; Light; Toxicity

The Emerging Role of the Mammalian Glycocalyx in Functional Membrane Organization and Immune System Regulation - Möckl, Leonhard (Frontiers in Cell and Developmental Biology, 2020)
All cells in the human body are covered by a dense layer of sugars and the proteins and lipids to which they are attached, collectively termed the “glycocalyx.” For decades, the organization of the glycocalyx and its interplay with the cellular state have remained enigmatic. This changed in recent years. Latest research has shown that the glycocalyx is an organelle of vital significance, actively involved in and functionally relevant for various cellular processes, that can be directly targeted in therapeutic contexts. This review gives a brief introduction into glycocalyx biology and describes the specific challenges glycocalyx research faces. Then, the traditional view of the role of the glycocalyx is discussed before several recent breakthroughs in glycocalyx research are surveyed. These results exemplify a currently unfolding bigger picture about the role of the glycocalyx as a fundamental cellular agent.
CRIS-Team Scopus Importer:2024-09-09
Keywords: cancer; cancer immune therapy; glycocalyx; immune system; immunosynapse; KRAS; membrane organization; siglecs

The Endothelial Glycocalyx Controls Interactions of Quantum Dots with the Endothelium and Their Translocation across the Blood-Tissue Border - Uhl, Bernd; Hirn, Stephanie; Immler, Roland; Mildner, Karina; Möckl, Leonhard; Sperandio, Markus; Bräuchle, Christoph; Reichel, Christoph A.; Zeuschner, Dagmar; Krombach, Fritz (ACS nano, 2017)
Advances in the engineering of nanoparticles (NPs), which represent particles of less than 100 nm in one external dimension, led to an increasing utilization of nanomaterials for biomedical purposes. A prerequisite for their use in diagnostic and therapeutic applications, however, is the targeted delivery to the site of injury. Interactions between blood-borne NPs and the vascular endothelium represent a critical step for nanoparticle delivery into diseased tissue. Here, we show that the endothelial glycocalyx, which constitutes a glycoprotein-polysaccharide meshwork coating the luminal surface of vessels, effectively controls interactions of carboxyl-functionalized quantum dots with the microvascular endothelium. Glycosaminoglycans of the endothelial glycocalyx were found to physically cover endothelial adhesion and signaling molecules, thereby preventing endothelial attachment, uptake, and translocation of these nanoparticles through different layers of the vessel wall. Conversely, degradation of the endothelial glycocalyx promoted interactions of these nanoparticles with microvascular endothelial cells under the pathologic condition of ischemia-reperfusion, thus identifying the injured endothelial glycocalyx as an essential element of the blood-tissue border facilitating the targeted delivery of nanomaterials to diseased tissue.
CRIS-Team Scopus Importer:2024-09-09
Keywords: blood-tissue border; endothelial glycocalyx; multiphoton in vivo microscopy; nanoparticle-endothelium interactions; nanoparticles; quantum dots; translocation

The glycocalyx regulates the uptake of nanoparticles by human endothelial cells in vitro - Möckl, Leonhard; Hirn, Stephanie; Torrano, Adriano A.; Uhl, Bernd; Bräuchle, Christoph; Krombach, Fritz (Nanomedicine, 2017)
Aim: To assess the role of the endothelial glycocalyx (eGCX) for the uptake of nanoparticles by endothelial cells. Methods: The expression of the eGCX on cultured human umbilical vein endothelial cells was determined by immunostaining of heparan sulfate. Enzymatic degradation of the eGCX was achieved by incubating the cells with eGCX-shedding enzymes. The uptake of 50-nm polystyrene nanospheres was quantified by confocal microscopy. Results: Human umbilical vein endothelial cells expressed a robust eGCX when cultured for 10 days. The uptake of both carboxylated and aminated polystyrene nanospheres was significantly increased in cells in which the glycocalyx was enzymatically degraded, while it remained at a low level in cells with an intact glycocalyx. Conclusion: The eGCX constitutes a barrier against the internalization of blood-borne nanoparticles by endothelial cells.
CRIS-Team Scopus Importer:2024-09-09
Keywords: endothelial cells; glycocalyx; heparan sulfate; live-cell imaging; nanoparticle-endothelium interactions; nanoparticles; polystyrene nanospheres

Treatment of acute myeloid leukemia models by targeting a cell surface RNA-binding protein - George, Benson M.; Eleftheriou, Maria; Yankova, Eliza; Perr, Jonathan; Chai, Peiyuan; Nestola, Gian Luca; Almahayni, Karim; Evans, Siân; Damaskou, Aristi; Hemberger, Helena; Lebedenko, Charlotta G.; Rak, Justyna; et al. (Nature Biotechnology, 2025)
Immunotherapies for acute myeloid leukemia (AML) and other cancers are limited by a lack of tumor-specific targets. Here we discover that RNA-binding proteins and glycosylated RNAs (glycoRNAs) form precisely organized nanodomains on cancer cell surfaces. We characterize nucleophosmin (NPM1) as an abundant cell surface protein (csNPM1) on a variety of tumor types. With a focus on AML, we observe csNPM1 on blasts and leukemic stem cells but not on normal hematopoietic stem cells. We develop a monoclonal antibody to target csNPM1, which exhibits robust anti-tumor activity in multiple syngeneic and xenograft models of AML, including patient-derived xenografts, without observable toxicity. We find that csNPM1 is expressed in a mutation-agnostic manner on primary AML cells and may therefore offer a general strategy for detecting and treating AML. Surface profiling and in vivo work also demonstrate csNPM1 as a target on solid tumors. Our data suggest that csNPM1 and its neighboring glycoRNA–cell surface RNA-binding protein (csRBP) clusters may serve as an alternative antigen class for therapeutic targeting or cell identification.
CRIS-Team Scopus Importer:2025-05-02

Tuning nanoparticle uptake: Live-cell imaging reveals two distinct endocytosis mechanisms mediated by natural and artificial EGFR targeting ligand - Mickler, Frauke M.; Möckl, Leonhard; Ruthardt, Nadia; Ogris, Manfred; Wagner, Ernst; Bräuchle, Christoph (Nano Letters, 2012)
Therapeutic nanoparticles can be directed to cancer cells by incorporating selective targeting ligands. Here, we investigate the epidermal growth factor receptor (EGFR)-mediated endocytosis of gene carriers (polyplexes) either targeted with natural EGF or GE11, a short synthetic EGFR-binding peptide. Highly sensitive live-cell fluorescence microcopy with single particle resolution unraveled the existence of two different uptake mechanisms; EGF triggers accelerated nanoparticle endocytosis due to its dual active role in receptor binding and signaling activation. For GE11, an alternative EGFR signaling independent, actin-driven pathway is presented. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2024-09-09
Keywords: EGF receptor; gene therapy; Live-cell imaging; polyplexes; targeting

Two high-pressure phases of SiS2 as missing links between the extremes of only edge-sharing and only corner-sharing tetrahedra - Evers, Jürgen; Mayer, Peter; Möckl, Leonhard; Oehlinger, Gilbert; Köppe, Ralf; Schnöckel, Hansgeorg (Inorganic Chemistry, 2015)
The ambient pressure phase of silicon disulfide (NP-SiS2), published in 1935, is orthorhombic and contains chains of distorted, edge-sharing SiS4 tetrahedra. The first high pressure phase, HP3-SiS2, published in 1965 and quenchable to ambient conditions, is tetragonal and contains distorted corner-sharing SiS4 tetrahedra. Here, we report on the crystal structures of two monoclinic phases, HP1-SiS2 and HP2-SiS2, which can be considered as missing links between the orthorhombic and the tetragonal phase. Both monoclinic phases contain edge- as well as corner-sharing SiS4 tetrahedra. With increasing pressure, the volume contraction (V/V) and the density, compared to the orthorhombic NP-phase, increase from only edge-sharing tetrahedra to only corner-sharing tetrahedra. The lattice and the positional parameters of NP-SiS2, HP1-SiS2, HP2-SiS2, and HP3-SiS2 were derived in good agreement with the experimental data from group-subgroup relationships with the CaF2 structure as aristotype. In addition, the Raman spectra of SiS2 show that the most intense bands of the new phases HP1-SiS2 and HP2-SiS2 (408 and 404 cm-1, respectively) lie between those of NP-SiS2 (434 cm-1) and HP3-SiS2 (324 cm-1). Density functional theory (DFT) calculations confirm these observations.
CRIS-Team Scopus Importer:2024-09-09

Wichard von Moellendorff: With logical acuity and systematic inflexibility Wichard von Moellendorff: Mit logischer Schärfe und systematischer Unbeugsamkeit - Evers, Jürgen; Möckl, Leonhard (Chemie in Unserer Zeit, 2015)
Plastification was in focus of research on metals and alloys in the first third of the 20th century. Wichard von Moellendorff built up a research laboratory at the "Allgemeine Elektricitätsgesellschaft" (AEG) in Berlin-Oberschöneweide in the "Kabelwerk Oberspree" (KWO). With systematic investigations on the metallographic and mechanic properties of metals and alloys he made substantial contributions to the scientific discussion of plastification. His results were partially contrary to the current opinion in metal science, but nevertheless true. Together with Czochralski he derived first conceptions on the mechanism for such deformations considering the crystalinity of the metals. After an interruption due to the first world war, Moellendorff started investigations as director of the "Staatliches Materialprüfungsamt" and the "Kaiser-Wilhelm-Institut für Metallforschung" on the plastic flow conus of metallic rods during rupture. This process was explained in 1929 by "turning, distortion and shearing of crystallographic planes". Polanyi at the Kaiser-Wilhem-Institut für Faserforschung, was able to explain the mechanism in 1932. Single atoms move step by step through the lattice on inclined positions and form dislocations. Together with neighbored atoms whole plains can be moved with a minimal energy through the crystal. With the dislocation mechanism, hammering, rolling and bending of metals and alloys can be explained. 1933 Polanyi left Nazi-Germany and became Professor in Manchester, Moellendorff was brave enough to make an affront against the Nazi regime in giving up the membership of the Kaiser-Wilhelm-Gesellschaft stating his personal opposition in an official letter which was not widespread behaviour of the German scientific and technical elite.
CRIS-Team Scopus Importer:2024-09-09